2022
DOI: 10.3390/ijms232012078
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonol Quercitrin Hinders GSK3 Activity and Potentiates the Wnt/β-Catenin Signaling Pathway

Abstract: The Wnt/β-catenin signaling pathway dictates cell proliferation and differentiation during embryonic development and tissue homeostasis. Its deregulation is associated with many pathological conditions, including neurodegenerative disease, frequently downregulated. The lack of efficient treatment for these diseases, including Alzheimer’s disease (AD), makes Wnt signaling an attractive target for therapies. Interestingly, novel Wnt signaling activating compounds are less frequently described than inhibitors, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…69 The lack of Wnt/β-catenin pathway signaling can indirectly promote neuroinflammation during aging, thus further promoting the development of AD. 70 Triggering receptors expressed on myeloid cells 2 (TREM2) activate microglia aggregation around plaques, thereby limiting Aβ diffusion and subsequent toxicity. Notably, TREM2 promotes microglia survival by activating the Wnt/β-catenin signaling pathway, indicating that the Wnt pathway is required for proper clearance of Aβ deposits.…”
Section: Wnt Signaling Pathway and Admentioning
confidence: 99%
See 3 more Smart Citations
“…69 The lack of Wnt/β-catenin pathway signaling can indirectly promote neuroinflammation during aging, thus further promoting the development of AD. 70 Triggering receptors expressed on myeloid cells 2 (TREM2) activate microglia aggregation around plaques, thereby limiting Aβ diffusion and subsequent toxicity. Notably, TREM2 promotes microglia survival by activating the Wnt/β-catenin signaling pathway, indicating that the Wnt pathway is required for proper clearance of Aβ deposits.…”
Section: Wnt Signaling Pathway and Admentioning
confidence: 99%
“…Therefore, their results revealed that quercitrin serves as a Wnt/β-catenin signaling pathway enhancer, which opens up new avenues for the treatment of AD. 70 Icariin II, one of the main active components of Herba Epimedii, has been shown to promote osteogenic differentiation of bone marrow-derived stromal cells. 157 It conveys a protective effect against brain I/R injury and cognitive deficits.…”
Section: Natural Compounds Regulate the Wnt Signaling Pathway In Ismentioning
confidence: 99%
See 2 more Smart Citations
“…2 Quercitrin has anti-inflammatory, anti-leishmanial, osteogenic, anti-nociceptive, and neuroprotective properties. 3 Research has shown that quercitrin inhibits GSK3 and enhances the signaling pathway Wnt/catenin. 3 Moreover, quercitrin has antioxidant and free radical scavenger activity, 4 and it inhibits acetylcholinesterase.…”
Section: Introductionmentioning
confidence: 99%